2011
DOI: 10.1371/journal.pmed.1001076
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and Access to Policy Élites: An Analysis of Tobacco Industry Documents

Abstract: Gary Fooks and colleagues undertook a review of tobacco industry documents and show that policies on corporate social responsibility can enable access to and dialogue with policymakers at the highest level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 43 publications
3
118
0
2
Order By: Relevance
“…Mas falar em defesa do ambiente lhes renderá maior credibilidade e reconhecimento social e, rapidamente, procuram ocupar esse espaço. Estudo desenvolvido na Inglaterra referente a estratégias de responsabilidade social da British American Tobacco (BAT) revelou que seu objetivo era ter acesso à elite política daquele país e assim influenciar nas decisões (FOOKS et al, 2011).…”
Section: Resultado E Discussãounclassified
“…Mas falar em defesa do ambiente lhes renderá maior credibilidade e reconhecimento social e, rapidamente, procuram ocupar esse espaço. Estudo desenvolvido na Inglaterra referente a estratégias de responsabilidade social da British American Tobacco (BAT) revelou que seu objetivo era ter acesso à elite política daquele país e assim influenciar nas decisões (FOOKS et al, 2011).…”
Section: Resultado E Discussãounclassified
“…Evidence suggests that these corporate social responsibility strategies are intended to facilitate access to government, co-opt nongovernmental organizations to corporate agendas, build trust among the public and political elite and promote untested, voluntary solutions over binding regulation. [11][12][13][14] Furthermore, corporate social responsibility strategies, including corporate philanthropy, have also been used to create divisions among public health professionals. 15,16 The two previous commentaries highlight this very danger.…”
Section: Round Table Discussionmentioning
confidence: 99%
“…10 Furthermore, in an attempt to silence any opposition to their products, tobacco companies co-opted interest groups that may potentially oppose tobacco industry-funded CSR programs to avoid possible criticism in future. 17,42 This study identified a wide range of CSR strategies implemented by the Big Food industry, many of which appear to offer community benefits such as the administration of grant funding schemes. However, it can also be argued that Big Food uses CSR strategies to build positive brand images and consumer preferences, which leads to decreased perceptions of harm and increased consumption of potentially harmful products.…”
mentioning
confidence: 99%